دور علماء فطاني في الدعوة الإسلامية خلال القرن الثالث عشر الهجري - Dohae, Muhammat Faosan; Kurniawan, Soleh (Dakwah, 2021)
The Muslim scholars of Patani have played significant role in leadership gridence and awareness of Muslim Ummah. They are the real heirs of the prophets who inherited their knowledge and deed. This research aims to study the role of Patani Muslim scholars of thirteen century according to Hijri calendar. It also aims to study their principles methods and roles in the field of Dakwah. To achieve these aims two researchers have performed theirresearch to find out principles, methods and role of     محمد فوزان دوهي بن عبد الصمد شيشيب صالح كونياوان |D a k w a t u na: J u r n a l D a k w a h d a n K o m u n i k a s i I s l a m2Muslim scholars of Patani in the field of Dawah and preparation of Doubt (Muslim preachers). To acheiria these aims of the research the both researchers used the descriptive and analytical methods. Among the results of the research: The Origins ofPatani Scholars Approach to Islamic Call and Their Role in Da`wah with the preacersand their role in Preparing theforPreaching. The researcher concluded this study byseveral conclusions, the most important of which are: They existeat the end of the 12th century H and the beginning of the 13th century H, They met witha number of scholars who visited the Sacred House, where they taught Muslim Malay children and were educated by scholars who lived in Makkah at the time. They are the Patani Jawi scholars who live in Makkah. Blessed are the Malay scholars who livedin the land of therevelation, seeking Islamic knowledge, education, Da`wah, andpreparing them as Islamicscholars, They wrote books in Arabic and Malay Javanese, After they were educated and increased in the Islamicknowledgeand Arab languages, some of them returned to their countries in their different places, and some of them set up traditional schools (Pondok) to teach their relatives and relatives and people who know ledged inIslamic religion and their teachings of pure islamicreligion and the call to the path of the righteous.